Analysis of the Framing of News Coverage of the Corruption Case of Nurdin Abdullah in Harian Fajar - Islamiah, Nia; Latief, Rahmawati; Hatta, Harmin (Jurnal Mercusuar, 2022)
This research aims to understand the framing of news coverage by Harian Fajar on the corruption case involving the infrastructure project of Nurdin Abdullah and to find out the strategies employed by Harian Fajar in constructing such news framing. The study employs a qualitative method and adopts Zhongdang Pan and Gerald M. Kosicki's framing analysis technique. Data is analyzed using four framing structures, namely, syntax, script, thematic, and rhetorical structures. News selection is done during the period of 28 February to 26 March 2021, and 9 news articles are chosen as the corpus of news coverage. Moreover, the study uses structured interview techniques to elaborate and complement the framing analysis results. The informant selected is the Jakarta bureau journalist of Harian Fajar, Taufik Hasyim. The results show that the news coverage by Harian Fajar is influenced by the psychological and sociological dimensions of journalists, as well as the media ideology, as seen from the framing of news coverage in terms of the use of headlines, source selection, media economics theory, and media political communication theory. Harian Fajar constructs news framing through four stages that uphold neutrality in news coverage.